Pan-Cancer Analyses Identify the CTC1-STN1-TEN1 Complex as a Protective Factor and Predictive Biomarker for Immune Checkpoint Blockade in Cancer - Wang, Lishuai; Ma, Tengfei; Liu, Weijin; Li, Heping; Luo, Zhenhua; Feng, Xuyang (Frontiers in Genetics, 2022)
The CTC1-STN1-TEN1 (CST) complex plays a crucial role in telomere replication and genome stability. However, the detailed mechanisms of CST regulation in cancer remain largely unknown. Here, we perform a comprehensive analysis of CST across 33 cancer types using multi-omic data from The Cancer Genome Atlas. In the genomic landscape, we identify CTC1/STN1 deletion and mutation and TEN1 amplification as the dominant alteration events. Expressions of CTC1 and STN1 are decreased in tumors compared to those in adjacent normal tissues. Clustering analysis based on CST expression reveals three cancer clusters displaying differences in survival, telomerase activity, cell proliferation, and genome stability. Interestingly, we find that CTC1 and STN1, but not TEN1, are co-expressed and associated with better survival. CTC1-STN1 is positively correlated with CD8 T cells and B cells and predicts a better response to immune checkpoint blockade in external datasets of cancer immunotherapy. Pathway analysis shows that MYC targets are negatively correlated with CTC1-STN1. We experimentally validated that knockout of CTC1 increased the mRNA level of c-MYC. Furthermore, CTC1 and STN1 are repressed by miRNAs and lncRNAs. Finally, by mining the connective map database, we discover a number of potential drugs that may target CST. In sum, this study illustrates CTC1-STN1 as a protective factor and provides broad molecular signatures for further functional and therapeutic studies of CST in cancer.